A Comparison of Dental Caries in Urban and Rural Children of the Riyadh Region of Saudi Arabia - Al-Rafee, Mohammed A.; AlShammery, Abdullah R.; AlRumikan, Ali S.; Pani, Sharat C. (Frontiers in Public Health, 2019)
Background and Aim: The data presented in this study aimed to document caries prevalence and severity among a representative sample of 6, 12, and 15 years old Saudi Children. Methodology: The study examined a total of 1,986 school children from 75 schools in urban and rural areas of Riyadh region, Saudi Arabia. Children having one or more dental caries lesion were used to determine prevalence of dental caries. Total number of decayed filled teeth (dft) was used to assess caries severity in the 6 years group while the DMFT was used to assess severity of dental caries at the 12 and 15 years age group. Results: The caries prevalence was 85.77% in the 6 years group, 64.98% in the 12 years group, and 71.35% in the 15 years group. Mean dft was 1.4 (SD ± 1.1). The mean DMFT was 1.72 (SD ± 0.49) at 12 years and 2.66 (SD ± 0.55) at 15 years. Both caries rate and severity were higher in rural areas than urban areas although the differences were not statistically significant. Conclusion: The results of this study suggest that the prevalence and severity of dental caries in Saudi Arabia remain high, when compared to global averages.